Could learning outcomes of the first course in accounting predict overall academic performance?. Issue 1 (2nd May 2017) - Alanzi, Khalid A.; Alfraih, Mishari M.
Abstract : Purpose: This study aims to question whether learning outcomes of the first course in accounting could predict the overall academic performance of accounting students as measured by their graduating grade point average (GPA). Design/methodology/approach: The sample of the present study was drawn from accounting students who were graduated during 2015 from a business college in Kuwait. Linear regression analysis was used to test the study's hypothesis. Findings: The results indicate that there was a statistically significant association between the grade earned in the first course in accounting and the graduating GPA, which explained the significant impact of the learning outcomes of the first course in accounting on the overall academic performance of accounting students as measured by their graduating GPA, with and without controls for other factors. Practical implications: The findings provide accounting educators with valuable insight into the significance of the outcomes of the first course in accounting, which would, in turn, lead to taking the necessary actions to enhance students' performances in this particular course, leading to improvements in the overall academic performance. The findings also provide academic researchers with a useful benchmark for future studies, as these findings would be expected to serve as a base for future studies in this area of research by re-examining the impact of students' performance in the first course in accounting on the overall academic performance of accounting students in different educational environments and/or using the findings of the current study for another comparative research study. Originality/value: Focusing on the impact of the learning outcomes of the first course in accounting on the overall academic performance of accounting students, rather than the other way around, the study contributes remarkably to the existing literature of accounting education, especially in developing countries such as Kuwait.